A study of Brownian relaxation time in magnetic nanofluids: a semi-analytical model - Osaci, Mihaela; Cacciola, Matteo (Multiscale and Multidisciplinary Modeling, Experiments and Design, 2024)
Magnetic nanofluids find application in various fields, including magnetic hyperthermia, which holds significant potential for non-invasive cancer treatment. The dynamics of magnetic nanoparticle systems under the influence of a magnetic field plays a crucial role in all applications, particularly in magnetic hyperthermia, and has been the subject of recent intensive research. Numerous studies investigating magnetic hyperthermia assume that the Brownian relaxation time is independent of the magnetic field and nanoparticle concentration. However, this modeling assumption can introduce errors in estimating certain parameters of interest. Consequently, these errors propagate in determining the effective relaxation time, which holds great importance in estimating quantities such as the Specific Absorption Rate and Intrinsic Loss Power Values for magnetic hyperthermia. This scientific paper presents a study that addresses these errors using a semi-analytical model. The experimental results obtained in our study contribute to the understanding of magnetic relaxation mechanisms in nanofluids under various conditions. Furthermore, these findings can aid in the development of accurate numerical evaluation models for practical applications.